Spinel assemblages in lunar meteorites Graves Nunataks 06157 and Dhofar 1528: Implications for impact melting and equilibration in the Moon's upper mantle. (28th November 2018) - Wittmann, Axel; Korotev, Randy L.; Jolliff, Bradley L.; Carpenter, Paul K.
Abstract: Magnesium‐rich spinel assemblages occur in the two lunar vitric breccia meteorites—Dhofar (Dho) 1528 and Graves Nunataks (GRA) 06157. Dho 1528 contains up to ~0.7 mm cumulate Mg‐rich spinel crystals associated with Mg‐rich olivine, Mg‐ and Al‐rich pyroxene, plagioclase, and rare cordierite. Using thermodynamic calculations of these mineral assemblages, we constrain equilibration depths and discuss an origin of these lithologies in the upper mantle of the Moon. In contrast, small, 10 to 20 μm spinel phenocryst assemblages in glassy melt rock clasts in Dho 1528 and GRA 06157 formed from the impact melting of Mg‐rich rocks. Some of these spinel phenocrysts match compositional constraints for spinel associated with "pink spinel anorthosites" inferred from remote sensing data. However, such spinel phenocrysts in meteorites and Apollo samples are typically associated with significant amounts of olivine ± pyroxene that exceed the compositional constraints for pink spinel anorthosites. We conclude that the remotely sensed "pink spinel anorthosites" have not been observed in the collections of lunar rocks. Moreover, we discuss impact‐excavation scenarios for the spinel‐bearing assemblages in Dhofar 1528 and compare the bulk rock composition of Dho 1528 to strikingly similar compositions of Luna 20 samples that contain ejecta from the Crisium impact basin.